Explaining Fluctuations in the Thrift Savings Fund Daily Balance at U.S. Treasury - Mark Skidmore; Camila Alvayay Torrejón; David Pare (Center for Economic Studies and Ifo Institute (CESifo), 2021)
In this paper we document and examine unusual fluctuations in the G-Fund, which is one of five funds available in a voluntary federal government employee retirement savings vehicle called the Thrift Savings Plan. The G-Fund is managed as “internally” held debt by the United States Department of Treasury. Our examination highlights two obscure facts about the G-Fund: 1) The fund is exclusively composed of one-day notes that Treasury redeems and reissues every business day. The daily turnover of the G-Fund results in about 55 trillion in debt reissuance annually; and 2) whenever the federal government is constrained by a debt ceiling, the G-Fund balance drops dramatically and typically does not return to pre-constraint balance levels until the debt ceiling is either expanded or suspended. We document these patterns and ask whether the G-Fund is managed in a way the represents the best interests of the fund contributors.
Keywords: G23; H23; H55; 330; thrift saving fund; public debt; debt ceiling; extraordinary measures; debt issuance; debt redemption